One-step fabrication for Mg-doped Cu2ZnSnS4 thin film via a facile ion-solution spraying approach - Chengxu Yan; Yu Sun; Jing Yang; Canyun Zhang; Fengchao Wang; Jin Chen (AIP Advances)
In this study, Mg-doped Cu2ZnSnS4 (CZTS) thin films were prepared by the ionic solution spraying method, which is simple, low cost, and low temperature. The samples were annealed at the optimal doping level. In this study, the relationship between the magnesium doping level, the annealing process conditions (temperature and duration), and various aspects of the sample properties was systematically investigated and discussed. These properties include film crystallinity, optical absorption properties, atomic ratios, and elemental composition. The results show that the Cu2Mg0.2Zn0.8SnS4 thin sample annealed at 500 °C for 10 min exhibits the best thin-film properties and has a relatively ideal atomic ratio. The replacement of Zn2+ ions with Mg2+ ions in the Cu2ZnSnS4 lattice leads to improved surface uniformity and densification, significant grain coarsening, and a reduction in the material’s optical bandgap to 1.37 eV. These materials demonstrate promising scalability for solar energy conversion applications, with cost-effective processing protocols and enhanced performance characteristics suggesting viable pathways for industrial implementation.